Conocimientos, actitudes y prácticas sobre los exámenes utilizados en la detección temprana del cáncer de próstata en hombres de dos comunas de Medellín (2012)
ABSTRACT: To identify the knowledge, attitudes, and practices associated with the exams used for early prostate cancer screening among men living in two suburbs in Medellín. Methodology: a cross-sectional study conducted using a stratified probability sampling and a guided survey with 38 questions. Percentages were used for the descriptive analysis. Likewise, the prevalence ratio and the confidence interval at 95% with a significance value of p < 0.05 were calculated in the bivariate analysis. Results: eighty-three surveys were conducted in 14 life clubs (social organizations of elderly people) in suburbs 2 and 4 of Medellín. The results showed that 68.7% of participants had adequate knowledge, 43.4 % an appropriate attitude, and 38.6 % adequate practices. It was observed that men with the adequate knowledge were 1.9 times (IC 95 % = 1.4-2.7) likely to also have an adequate attitude compared to those with inadequate knowledge. Similarly, men with adequate attitude were 1.8 times (IC 95 % = 1.2-2.7) likely to also have adequate practices compared to men with an inadequate attitude. Discussion: It is necessary to strengthen the interventions aiming to prevent prostate cancer among the poorest and most vulnerable men, since they are less likely to have adequate knowledge, attitude, and practices.